Die Rolle von Kooperationen im Gewässerschutz aus Sicht der Wasserversorgungsunternehmen; The Role of Cooperations in Water Protection from the Water Suppliers' Perspective - Katja Beck; Andrea Knierim (German Journal of Agricultural Economics (GJAE), 2019)
– With their cooperations in Germany, farmers and water supply companies have a special role in securing the drinking water supply and in reducing the nitrate content. Farmers contribute to environmental protection by reducing the amount of fertiliser used, but despite the fact that less mineral fertiliser is used, they have no financial disadvantage due to the compensation payments. Water supply companies thus have less expenses for water treatment and can use these financial savings for compensation payments. Changing political framework conditions such as the amendment of the Fertiliser Ordinance and the Nitrate Report 2016, published in January 2017, gave rise to the investigation of such cooperations between farmers and water supply companies. This study focuses on the challenges and success factors of cooperations from the point of view of the water supply companies. For this purpose, a qualitative empirical study was carried out with experts from the water industry. The interview partners were selected according to the snowball sampling and convenience sampling. The data collection took place in the form of guided expert interviews. The data evaluation was performed on the basis of the qualitative content analysis according to Mayring with category formation. As a result, it can be summarised that the political framework conditions and their changes have a major influence on cooperations in water management. Due to the voluntary nature of cooperations, not all farmers working in water protection areas are involved in a cooperation. Successful communication among all participants is both a framework condition and a success factor, without which cooperations cannot function in the long term. The heterogeneous organisational forms of cooperations at the national level can be regarded as advantages and disadvantages in that, on the one hand, site specifics can be taken into account in the design of cooperations and, on the other hand, a guideline for general cooperation standards and financing is lacking.
Keywords: 330